Stock Analysis of Kroyo Crab in Cirebon Waters, Gebang Mekar Village, Gebang District, Cirebon Regency - Achmad Mufidh Karomatullah; Aninditia Sabdaningsih; Suradi Wijaya Saputra (The Islamic Education and Multiculturalism Foundation, 2023)
The development of crabs in Cirebon Regency is one of the important indicators in increasing fisheries production, the increase is based on the high market demand for crab commodities, especially kroyo crabs, causing an impact on the crab population. This research was carried out from February 2022 to March 2023 in 3 sub-districts, namely Suranenggala, Mundu and Gebang. This study aims to determine the stock of kroyo crabs which include carapace width and weight, growth, condition factors, mortality, and exploitation rate. The method used is direct observation of special fishermen catching kroyo crabs. The key crabs measured during the study amounted to 360 individuals with a carapace width range of male crabs of 27-44 mm and female crabs of 28-51 mm, with a frequency distribution of 8 class intervals from December 2022 to February 2023. Tools used to analyze stock conditions using the help of FISAT II and Microsoft Excel software. The first size results were caught in males (L50%=34,18mm) with more than half the asymptotic length (½L∞=23,75mm), while in females (L50%=41,08mm) greater than half the asymptotic length (½L∞=25,75mm). The carapace-weight width relationship of the male crab is W = 1,227L0,510 and the female crab W = 0,371L0,896. Conditions factors in male crabs (1,007) and females (1,008) have the same level of mon-decency. Growth equation of Von Bertalanffy male crab Lt=47,25[1- e(-0,79(t+0,179))] and female crabs Lt=51,45[1- e(-0,99(t+0,138))], So it can be stated that the growth of female crabs is faster than that of male crabs. In male crabs, the Total Mortality Rate (Z) was obtained at 2.99 per year, natural mortality (M) of 1.39 per year, and arrest mortality (F) of 1.60 per year. While in female crabs Z = 2.44 per year, M = 1.57 per year, F = 1.60 per year. The exploitation rate (E) of male crabs was obtained at 0.54 per year and females at 0.35 which means that the capture of Charybdis anisodon waters is still a tendency of underfishing. The pattern of adding new male crabs in Cirebon waters has two peaks, namely in April and August, with female crabs in July. Based on the results of this study, it can be concluded that the stock condition in Cirebon waters is still in the category of suitable for fishing for fishermen.